The wolf and the woodsman - Reid, Ava (Harper Voyager, an imprint of HarperCollinsPublishers, 2021)
"Follows a young pagan woman with hidden powers and a one-eyed captain of the Woodsmen as they form an unlikely alliance to thwart a tyrant"--